2019
DOI: 10.1123/mc.2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Chuan and Brisk Walking Exercise on Balance Ability in Elderly Women: A Randomized Controlled Trial

Abstract: This study aims to investigate the effects of Tai Chi Chuan (TCC) and brisk walking (BW) on balance and training duration for the two exercises to significantly improve balance. A total of 48 elderly women were randomly divided into three groups. The TCC and BW groups completed a 60-min intervention training program with five sessions weekly for 16 weeks. Single-leg standing balance was tested every 4 weeks. Results showed that all the variables with eyes open improved on the eighth week (p < .05) in the TCC g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 38 publications
1
23
0
2
Order By: Relevance
“…The importance of Physical activity are many as it diminishes the risk of various non-communicable and chronic health conditions, which includes heart disease, hypertension, type 2 diabetes, colon, post-menopausal breast and endometrial cancers, stroke, osteoporosis, osteoarthritis, depression, falls and disability in the elderly people 12,14,16,17,19,[21][22][23][24]26,[30][31][32][33][34][35][36][37][38] . From the extant review, it is therefore concluded that physical activities have numerous advantages for the prevention and management of many health-related conditions been faced by the elderly people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of Physical activity are many as it diminishes the risk of various non-communicable and chronic health conditions, which includes heart disease, hypertension, type 2 diabetes, colon, post-menopausal breast and endometrial cancers, stroke, osteoporosis, osteoarthritis, depression, falls and disability in the elderly people 12,14,16,17,19,[21][22][23][24]26,[30][31][32][33][34][35][36][37][38] . From the extant review, it is therefore concluded that physical activities have numerous advantages for the prevention and management of many health-related conditions been faced by the elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study on the effects of Tai Chi Chuan, a form of exercise originating in Asia and 'Brisk Walking Exercise on Balance Ability in Elderly Women' revealed that 12 and 16 weeks of Tai Chi Chuan and brisk walking respectively were essential to improve balance (which is a major factor in risk of fall) with eyes closed among the women aged 60-70 years. Exercise can either be done alone or in groups, although, group exercise is the best as older adults who participate in group exercise receives additional benefits related to falls prevention compared with those who exercise alone 37,38 .…”
Section: The Role Of Physical Activity In the Prevention Of Fallsmentioning
confidence: 99%
“…Mengurangi risiko kardiovaskular pada pasien, efektif mengurangi kadar gula darah (20) (12), efektif menurunkan tekanan darah terutama pada latihan intensitas tingkat sedang (26). Efektivitas brisk walking lainnya diantaranya, mencegah penurunan stabilitas postural dan mengurangi risiko jatuh dan meningkatkan kemampuan keseimbangan lansia dan daya tahan berjalan (toleransi olahraga) hingga 45% (21) (23) (25).…”
Section: Efektivitas Brisk Walkingunclassified
“…Regular physical exercise is associated with improved health-related quality of life, maintaining health [2], and the functional capacity of the elderly, as well as being a factor in reducing mortality [30], decreasing the risk of osteoporosis, falls, and fractures [24]. Moreover, studies reveal improvements due to exercise in several specific variables such as speed [14], balance in walking [31], aerobic endurance [5], flexibility [12], muscle strength, and quality of life [36].…”
Section: Introductionmentioning
confidence: 99%